Triptolide inhibits donor‐specific antibody production and attenuates mixed antibody‐mediated renal allograft injury. Issue 5 (29th December 2017) - Zhao, Daqiang; Li, Siwen; Liao, Tao; Wei, Yuan; Liu, Mingyu; Han, Fei; Luo, Zihuan; Liu, Xiaonan; Sun, Qiquan
Abstract : Donor‐specific antibodies (DSAs) are major mediators of renal allograft injury, and strategies to inhibit DSAs are important in promoting long‐term graft survival. Triptolide exhibits a wide spectrum of antiinflammatory and immunosuppressive activities, and in autoimmune diseases it inhibits autoantibody levels. In this study, we investigated the suppressive role of triptolide in the generation of DSAs in transplant recipients. We found that triptolide treatment of skin allograft recipients in mice significantly suppressed the development of circulating anti‐donor‐specific IgG and effectively alleviated DSA‐mediated renal allograft injury, which led to prolonged allograft survival. In vitro studies revealed that triptolide inhibited the differentiation of B cells into CD138 + CD27 ++ plasma cells; reduced the levels of IgA, IgG, and IgM secreted by plasma cells; and repressed somatic hypermutation and class switch recombination of B cells. Moreover, triptolide‐treated recipients showed reduced numbers of B cells, plasma cells, and memory B cells in spleens and decreased numbers of T, B, natural killer (NK) cells, and macrophages infiltrating grafts. These findings highlight the importance of triptolide in suppressing DSAs and establish triptolide as a novel therapeutic agent for antibody‐mediated allograft rejection. Abstract : Triptolide attenuates antibody‐mediated renal allograft injury by suppressing B cell activation and donor‐specific antibody development, accompanied by a reduction in multiple graft‐infiltrating inflammatory cells.